Performance of Kenyan athletes in mountain versus flat marathon running - An example in Switzerland - Harm, C.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R.; Onywera, V. (Journal of Human Sport & Exercise, 2013)
The purpose of this study was to compare running performance of Kenyans in a flat city marathon and a mountain marathon in Switzerland. Running times of top three overall Kenyan runners were compared with running times of top three overall runners of other nations in a mountain and a flat marathon held in Switzerland between 2003 and 2011. In the mountain marathon top three male Kenyans achieved with 199±23min the 11th fastest running time behind athletes from Italy (177±1min), Switzerland (179±0min), France (186±5min), Great Britain (189±3min), Mexico (189±3min), Germany (192±5min), Czech Republic (195±13min), Morocco (195±7min), USA (196±6min) and Hungary (198±8min). Female Kenyan athletes did not even participate in the mountain marathon. In the city marathon top three male Kenyan athletes achieved the second fastest running time (130±1min) behind Swiss athletes (129±1min), Kenyan female runners had the fifth fastest running time (158±4min) behind athletes from Russia (153±2min), Ethiopia (154±2min), Switzerland (155±2min) and Poland (155±4min). To summarize, Switzerland, Kenyans achieved not the fastest running times in a mountain marathon while they attained the second fastest running times in flat marathon.